Implementasi Pembacaan Asmaul Husna dalam Membentuk Karakter Siswa di MTs Miftahul Hasan Wangkal Probolinggo - Syarifa, Helmalia; Yunus, Moch.; Zaini, Bahruddin (YASIN, 2025)
Character education is a crucial foundation in shaping students into individuals with noble character, particularly amid the moral decline of younger generations and the growing need for educational models that instill religious values. This study aims to examine the implementation of Asmaul Husna recitation in character development at MTS Miftahul Hasan. Asmaul Husna, representing the Most Beautiful Names of Allah, contains moral and spiritual values that can be instilled from an early age. The study employs a qualitative approach with a descriptive method, utilizing observation, interviews, and documentation for data collection. Data were analyzed through data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The research subjects included students and teachers. The findings reveal that the daily morning recitation of Asmaul Husna contributes significantly to the development of students’ Islamic character. Supporting factors include active student participation, the role of teachers, and the availability of facilities, while key obstacles involve lack of discipline, delayed implementation, and limited awareness among some students. The study concludes that the recitation of Asmaul Husna is an effective habituation practice for fostering students’ religious character and can serve as a model for strengthening character education in school environments.